ナンキョク セツジョウ シャ ニ ツイテ - 細谷, 昌之; ホソヤ, マサユキ; Hosoya, Masayuki (1985)
P(論文) この報告は, 日本南極地域観測隊が行う内陸の調査旅行および海氷上の調査旅行, ならびに昭和基地または昭和基地周辺において貨物の輸送などに使う雪上車(南極雪上車)について, 具備しなければならない特性, 国内の雪上車市場との関係, 南極地域観測が始まってから現在までの変遷と現状, および南極雪上車が避けられない問題などの概要を述べたものである。 This paper describes the characteristics of the antarctic snow vehicle, domestic market of the snow vehicle, changes and the present situation of the snow vehicle after the establishment of the antarctic station and some problems of the antarctic snow vehicle. Japanese Antarctic Research Expedition is presently equipped with three types of snow vehicle, SM50S, SM40S and SM20S. These snow vehicles are used in the inland trips and sea ice exploring, in transportation of cargo to inland station, as well as to Syowa Station and its outskirts. departmental bulletin paper